The influence of problem based learning towards social science learning outcomes viewed from learning interest - Berti Dyah Permatasari; Gunarhadi Gunarhadi; Riyadi Riyadi (Institute of Advanced Engineering and Science, 2019)
The aim of this study is to determine the influences of Problem Based Learning and learning interest at improving the cognitive learning outcomes in social science of fourth-grade elementary school students. This study is a quasi-experiment study with pre-test and post-test control group design. The sample collection is taken with stratified cluster random sampling technique. The sample of this study is 109 fourth-grade elementary school students, consisted of 50 students from experiment group and 59 students from control group. The students from experiment group are given the application of Problem Based Learning, while the students in control group are given the application of Direct Instruction. The data collection is carried by using the instruments of social science learning outcomes test and social science learning interest questionnaire. The validity of test and questionnaire instruments is carried by expert judgement. The difficulty level, distinguishing power, and reliability of test instrument is tested by using ITEMAN application. The internal consistency and reliability of questionnaire instrument is tested by using SPSS application. The data is analysed by using two-way anova. The outcomes of the study show that PBL and learning interest contribute significant impact towards social science learning outcomes of elementary school students.